The Use of Game-Based Learning on Student’s Speaking Skill and Speaking Anxiety: An Experimental Research at Seventh Grade of MTs YASMU - Chadafi, Muammar (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Speaking is one of important skill that we have mastered in English. It’s made us easier to get a new friend. Besides, speaking is a difficult skill to master for learners because speaking combines the parts of writing and listening. This research goals at investigating the use of game-based learning on students’ speaking skill and students’ speaking anxiety. The researcher used a quantitative method with a pre-experimental design by using the validity and reliability test instrument. The population in this research was seventh class grade MTs YASMU Manyarejo Manyar Gresik. After collecting data using a test, one class was given a pre-test before treatment and a post-test after treatment. Then data analysis using SPSS or Manual counting with the formula paired simple t-test. The result showed that the experimental group scores had a significant difference before being taught the game-based learning method. It can be said with more than 95% confidence, that the anxiety means in control and experimental group before using game-based learning was not significantly different. Therefore, the results revealed that balancing as a stress-free tool of learning has the potential of reducing students’ anxiety to improve their speaking skill.